LEVERAGE RATIOS AND STOCK RETURNS OF DEPOSIT MONEY BANKS IN NIGERIA - Vincent Afure Akpotor (Indian Journal of Economics and Financial Issues, 2025)
Financial statement contains the financial information about the operations of firms over a period, as well as the value of assets, liabilities and equity at a specific date. The major objective of this study is to ascertain the relationship between leverage ratios and stock returns of deposit money banks in Nigeria for the period 2011-2022. The study used total debt to asset ratio, total debt to equity ratio as independent variables. While, stock returns of deposit money banks was used as the dependent variable. The study used secondary data obtained from the financial statement of sampled banking firms and the records of Nigeria Exchange Limited (NGX) for analysis. The study Generalized Method of Moments (GMM) technique for data analysis. Findings from the analysis revealed that total debt/asset ratio had positive and significant relationship with stock returns of deposit money banks in Nigeria, while total debt/equity ratio had negative and no significant relationship with stock returns. The positive relationship as exhibited by debt asset ratio confirm the asset transformation process of bank operations, especially as deposit transformed to loan becomes the assets of banks. While, the indirect relationship as shown by debt equity ratio revealed the danger posed by increase in debt in relation to equity, if debt is not linked to investment in viable assets. Therefore, the study recommended that; Deposit Money Banks should invest created liabilities in verified-profitable choices of assets, to generate “above-cost” returns and ensure favourable leverage; and cost of debts should be properly analyzed prior to procurement. JEL: G10, GII, G53, F65. Keywords: Leverage Ratios, Stock Returns, Deposit Money Banks, Total Debt/Asset ratio, Total Debt Equity Ratio.
Corporate Finance